n-3 fatty acids and rosiglitazone improve insulin sensitivity through additive stimulatory effects on muscle glycogen synthesis in mice fed a high-fat diet - Kuda, O; Jelenik, T; Jilkova, Z; Flachs, P; Rossmeisl, M; Hensler, M; Kazdova, L; Ogston, N; Baranowski, M; Gorski, J; Janovska, P; Kus, V; et al. (Diabetologia, 2009)
AIMS/HYPOTHESIS: Fatty acids of marine origin, i.e. docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) act as hypolipidaemics, but they do not improve glycaemic control in obese and diabetic patients. Thiazolidinediones like rosiglitazone are specific activators of peroxisome proliferator-activated receptor gamma, which improve whole-body insulin sensitivity. We hypothesised that a combined treatment with a DHA and EPA concentrate (DHA/EPA) and rosiglitazone would correct, by complementary additive mechanisms, impairments of lipid and glucose homeostasis in obesity. METHODS: Male C57BL/6 mice were fed a corn oil-based high-fat diet. The effects of DHA/EPA (replacing 15% dietary lipids), rosiglitazone (10 mg/kg diet) or a combination of both on body weight, adiposity, metabolic markers and adiponectin in plasma, as well as on liver and muscle gene expression and metabolism were analysed. Euglycaemic-hyperinsulinaemic clamps were used to characterise the changes in insulin sensitivity. The effects of the treatments were also analysed in dietary obese mice with impaired glucose tolerance (IGT). RESULTS: DHA/EPA and rosiglitazone exerted additive effects in prevention of obesity, adipocyte hypertrophy, low-grade adipose tissue inflammation, dyslipidaemia and insulin resistance, while inducing adiponectin, suppressing hepatic lipogenesis and decreasing muscle ceramide concentration. The improvement in glucose tolerance reflected a synergistic stimulatory effect of the combined treatment on muscle glycogen synthesis and its sensitivity to insulin. The combination treatment also reversed dietary obesity, dyslipidaemia and IGT. CONCLUSIONS/INTERPRETATION: DHA/EPA and rosiglitazone can be used as complementary therapies to counteract dyslipidaemia and insulin resistance. The combination treatment may reduce dose requirements and hence the incidence of adverse side effects of thiazolidinedione therapy.
Keywords: Eicosapentaenoic Acid; Insulin; Male; inzulin; kyseliny dokosahexaenové; Fatty Acids, Omega-3; kukuřičný olej; thiazolidindiony; omega-3 mastné kyseliny; Muscle, Skeletal; Rosiglitazone; mužské pohlaví; Dietary Fats; Corn Oil; rosiglitazon; kosterní svaly; glykogen; dietní tuky; Thiazolidinediones; hypoglykemika; Animals; kyselina eikosapentaenová; Docosahexaenoic Acids; zvířata; porucha glukózové tolerance; myši inbrední C57BL; myši; Hypoglycemic Agents; Mice, Inbred C57BL; Glycogen; Mice; Glucose Intolerance